Seeding and Emergence of Composite Skyrmions in a van der Waals Magnet. Issue 12 (8th February 2023) - Powalla, Lukas; Birch, Max T.; Litzius, Kai; Wintz, Sebastian; Yasin, Fehmi S.; Turnbull, Luke A.; Schulz, Frank; Mayoh, Daniel A.; Balakrishnan, Geetha; Weigand, Markus; Yu, Xiuzhen; Kern, Klaus; et al.
Abstract: Topological charge plays a significant role in a range of physical systems. In particular, observations of real‐space topological objects in magnetic materials have been largely limited to skyrmions – states with a unitary topological charge. Recently, more exotic states with varying topology, such as antiskyrmions, merons, or bimerons and 3D states such as skyrmion strings, chiral bobbers, and hopfions, have been experimentally reported. Along these lines, the realization of states with higher‐order topology has the potential to open new avenues of research in topological magnetism and its spintronic applications. Here, real‐space imaging of such spin textures, including skyrmion, skyrmionium, skyrmion bag, and skyrmion sack states, observed in exfoliated flakes of the van der Waals magnet Fe3− x GeTe2 (FGT) is reported. These composite skyrmions may emerge from seeded, loop‐like states condensed into the stripe domain structure, demonstrating the possibility to realize spin textures with arbitrary integer topological charge within exfoliated flakes of 2D magnets. The general nature of the formation mechanism motivates the search for composite skyrmion states in both well‐known and new magnetic materials, which may yet reveal an even richer spectrum of higher‐order topological objects. Abstract : Composite skyrmions with non‐unitary topological charge are imaged in exfoliated flakes of the 2D magnet Fe3 GeTe2 . Transitions between skyrmion, skyrmionium, skyrmion bag, and skyrmion sack states reveal details concerning the topological protection of the observed objects. The general nature of the seeding and emergence formation mechanism highlights that composite skyrmions may await discovery in both well‐known and future skyrmion materials.